Labour Activism and Social Movement Unionism in the Gig Economy. Food Delivery Workers Struggles in Italy - Riccardo Emilio Chesta; Lorenzo Zamponi; Carlotta Caciagli (Partecipazione e Conflitto, 2019)
This article aims to explore the forms of collective actions that are emerging in new sectors of digital capitalism. In particular, it enquires into the mobilisation of food delivery workers that has been developing since 2016 in four Italian cities: Milan, Turin, Bologna and Florence. Despite the high level of precarisation and atomisation that characterise this subset of gig economy jobs, the so-called riders were able to organise into self-organised workers' collectives, which not only gave rise to many protest events, but also drew the attention of the institutions and the media. What are the conditions and the strategies that made this possible? And, more broadly, what does this case tell us about the possibility of labour activism in gig economy work? We argue that the high level of activation of food delivery workers is to be related to their capability to provide resources for reconstructing social ties among workers and, in turn, for translating them into political engagement and contentious action. This is realised through the combination of three factors that will be scrutinised in the paper. The analysis points out that although precarisation creates significant obstacles to organisation and mobilisation, collective action does actually take place also in the gig economy, in certain conditions.